The Barents Sea System 2021
DOI: 10.29006/978-5-6045110-0-8/(27)
|View full text |Cite
|
Sign up to set email alerts
|

Zoobentos of the Barents sea

Abstract: Аннотация на английском языке: Based on the analysis of retrospective and recent materials, the species richness of the bottom fauna and the long-term variability of the quantitative characteristics of zoobenthos of the Barents Sea are considered. The role of key taxa in the formation of benthic biomass and its trophic structure is indicated. The negative impact of bottom trawling on benthic fauna is shown and the most vulnerable areas in the basin are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 0 publications
1
15
1
Order By: Relevance
“…The study used valid species names according to the World Register of Marine Species (WoRMS) (https: //www.marinespecies.org, 20 March 2023 accessed). Information on the biogeographic affiliation of bryozoan species was taken from the literature [19,23,24,40,41].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study used valid species names according to the World Register of Marine Species (WoRMS) (https: //www.marinespecies.org, 20 March 2023 accessed). Information on the biogeographic affiliation of bryozoan species was taken from the literature [19,23,24,40,41].…”
Section: Methodsmentioning
confidence: 99%
“…Despite a long history of zoobenthos research in the Arctic, the faunistic composition and distribution of bryozoans in this region remain insufficiently studied, even though about 90% of the species inhabiting the seas in this region are currently known [49]. Previous studies in the Barents Sea have shown that only about 40-50 bryozoan species formed dense assemblages [19], which accounted for less than 10% of overall bryozoan species richness in the Arctic [50]. The diversity of species that contribute appreciably to the total zoobenthos biomass in the coastal waters was even much lower.…”
Section: Diversity Of Biomass-dominating Key Bryozoan Species and The...mentioning
confidence: 99%
See 1 more Smart Citation
“…After this discovery, all major X-ray observatories such as INTEGRAL, NICER and Insight-HXMT (Chen et al 2019;Lepingwell et al 2019;Sanna et al 2019) conducted follow-up observations to understand the nature of the source. Optical and radio counterparts (Denisenko et al 2019;Russell et al 2019) have been reported for the source and the multi-wavelength properties suggested that the source is a BHXRB (Russell et al 2019;Carotenuto et al 2021). NICER monitoring observations showed outburst evolution similar to what is commonly observed in BHXRBs and during the outburst phase, the source exhibited different types of quasi-periodic oscillations (QPOs) as well (Belloni et al 2020;Zhang et al 2020).…”
Section: Introductionmentioning
confidence: 90%
“…Due to their economic significance, Iceland scallops have undergone extensive research in the Barents Sea, resulting in a complicated understanding of many aspects of their life cycle. Population dynamics, patterns of reproduction, growth rates, feeding habits, and mortality rates have all received detailed attention [17,23,24]. Furthermore, particular aspects of technological processing have also been examined [17].…”
Section: Introductionmentioning
confidence: 99%